Analyzing X-ray tomographies of granular packings - Weis, Simon; Schröter, Matthias (Review of Scientific Instruments, 2017)
Starting from three-dimensional volume data of a granular packing, as, e.g., obtained by X-ray Computed Tomography, we discuss methods to first detect the individual particles in the sample and then analyze their properties. This analysis includes the pair correlation function, the volume and shape of the Voronoi cells, and the number and type of contacts formed between individual particles. We mainly focus on packings of monodisperse spheres, but we will also comment on other monoschematic particles such as ellipsoids and tetrahedra. This paper is accompanied by a package of free software containing all programs (including source code) and an example three-dimensional dataset which allows the reader to reproduce and modify all examples given.
EAM Import::2019-03-13

An invariant distribution in static granular media - Schröter, Matthias; Aste, T.; Di Matteo, Tiziana; Saadatfar, Mohammad; Senden, T.J.; Swinney, Harry L. (EPL - Europhysics Letters, 2007)
We have discovered an invariant distribution for local packing configurations in static granular media. This distribution holds in experiments for packing fractions covering most of the range from random loose packed to random close packed, for bead packs prepared both in air and in water. Assuming only that there exist elementary cells in which the system volume is subdivided, we derive from statistical mechanics a distribution that is in accord with the observations. This universal distribution function for granular media is analogous to the Maxwell-Boltzmann distribution for molecular gasses.

Controlling the Formation of Capillary Bridges in Binary Liquid Mixtures - Schröter, Matthias; Gögelein, Christoph; Brinkmann, Martin; Herminghaus, Stephan (Langmuir, 2010)
We study the formation of capillary bridges between micrometer-sized glass spheres immersed in a binary liquid mixture using bright field and confocal microscopy. The bridges form upon heating due to the preferential wetting of the hydrophilic glass surface by the water-rich phase. If the system is cooled below the demixing temperature, the bridges disappear within a few seconds by intermolecular diffusion. Thus, this system oilers the opportunity to switch the bridges on and off and to tune precisely the bridge volume by altering the temperature in a convenient range. We measure the bridge geometry as a function or the temperature from bright field images and calculate the cohesive force. We discuss the influence of the solvent composition on the bridge formation temperature, the strength of the capillary force. and the bridge volume growth rate. Furthermore, we find that the onset of bridge formation coincides with the water-lutidine bulk coexistence curve.

Correction of beam hardening in X-ray radiograms - Baur, Manuel; Uhlmann, Norman; Pöschel, Thorsten; Schröter, Matthias (Review of Scientific Instruments, 2019)
The intensity of a monochromatic X-ray beam decreases exponentially with the distance it has traveled inside a material; this behavior is commonly referred to as Beer-Lambert's law. Knowledge of the material-specific attenuation coefficient mu allows us to determine the thickness of a sample from the intensity decrease the beam has experienced. However, classical X-ray tubes emit a polychromatic bremsstrahlung-spectrum. And the attenuation coefficients of all materials depend on the photon energy: photons with high energy are attenuated less than photons with low energy. In consequence, the X-ray spectrum changes while traveling through the medium; due to the relative increase in high energy photons, this effect is called beam hardening. For this varying spectrum, the Beer-Lambert law only remains valid if mu is replaced by an effective attenuation coefficient mu(eff) which depends not only on the material but also on its thickness x and the details of the X-ray setup used. We present here a way to deduce mu(eff)(x) from a small number of auxiliary measurements using a phenomenological model. This model can then be used to determine an unknown material thickness or in the case of a granular media its volume fraction. Published under license by AIP Publishing.
CRIS-Team WoS Importer:2019-03-20

Correlation between Voronoi volumes in disc packings - Schröter, Matthias; Zhao, Song-Chuan; Sidle, Stacy; Swinney, Harry L. (EPL - Europhysics Letters, 2012)
We measure the two-point correlation of free Voronoi volumes in binary disc packings, where the packing fraction phi(avg) ranges from 0.8175 to 0.8380. We observe short-ranged correlations over the whole range of phi(avg) and anticorrelations for phi(avg) > 0.8277. The spatial extent of the anticorrelation increases with phi(avg) while the position of the maximum of the anticorrelation and the extent of the positive correlation shrink with phi(avg). We conjecture that the onset of anticorrelation corresponds to dilatancy onset in this system. Copyright (C) EPLA, 2012

Der Paranuss-Effekt - Schröter, Matthias; Ulrich, Stephan (Physik in unserer Zeit, 2007)
Granulare Medien, wie Sand, Salz, Kohle oder Kaffeebohnen, lassen sich durch vertikales Schütteln entmischen. In Abhängigkeit von der Schüttelamplitude sammeln sich die größeren Teilchen entweder an der Oberfläche (der sogenannte Paranuss-Effekt), oder sie sinken nach unten (inverser Paranuss-Effekt). Mit Experimenten, Computersimula- tionen und Theorie ist es jüngst gelungen, die zu diesem Verhalten führenden Mechanismen zu identifizieren [1, 2].

Die Fingermorphologie in der Elektrodeposition, ein komplexes Grenzflächenphänomen - Schröter, Matthias (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2003)
English: Recently a fingering morphology, resembling the hydrodynamic Saffman-Taylor instability, was identified in the quasi-two-dimensional electrodeposition of copper by M. Lòpez-Salvans et al. [Phys. Rev. Lett. 76, 4062 (1996)]. This thesis tries to elucidate the underlying mechanism by measuring the dispersion relation of the growing front. The instability is accompanied by gravity-driven convection rolls at the electrodes, which are examined using particle image velocimetry. While at the anode the theory presented by Chazalviel et al. [J. Electroanal. Chem. 407, 61 (1996)] describes the convection roll, the flow field at the cathode is more complicated because of the growing deposit. In particular, the analysis of the orientation of the velocity vectors reveals some lag of the development of the convection roll compared to the finger envelope. In thin-layer electrodeposition the dissipated electrical energy leads to a substantial heating of the ion solution. Measurements of the resulting temperature field by means of an infrared camera indicate, that its properties correspond closely with the development of the concentration field. In particular, we find that the thermal gradients at the electrodes act similar to a weak additional driving force to the convection rolls driven by concentration gradients.   Deutsch: Die elektrolytische Abscheidung von Metallen in dünnen Zellen führt in Abhängigkeit von den experimentellen Parametern zu einer Vielzahl unterschiedlicher Morphologien. M. Lòpez-Salvans et al. [Phys. Rev. Lett. 76, 4062 (1996)] beobachten erstmals das Wachstum eines Deposits mit einer fingerartigen Hüllkurve. Als Elektrolyt dient eine Kupfersulfatlösung mit einer geringen Beigabe von Natriumsulfat. Unmittelbar vor dem wachsenden Deposit bildet sich eine Kupferhydroxidschicht aus. Die so entstehende Situation weist Ähnlichkeit mit der Saffman-Taylor-Instabilität auf, bei der ebenfalls Finger entstehen. Ziel der vorliegenden Arbeit ist es, durch Messungen, die als Grundlage einer theoretischen Modellierung dienen können, zum Verständnis des Fingerbildungsphänomens beizutragen. Hierzu werden drei verschiedene Fragestellungen untersucht: (1) Zur Charakterisierung der initialen Phase der Instabilität wird die zeitliche Entwicklung der Fingerhüllkurve vermessen. Die einzelnen Moden des Fourierspektrums der Grenzlinie zeigen ein exponentielles Wachstum. Die Abhängigkeit der Wachstumsraten der Moden von deren Wellenzahl ergibt die Dispersionsrelation. Durch die gezielte Anregung einer kurzwelligen Mode mit Hilfe einer strukturierten Elektrode kann auch eine negative Wachstumsrate genau bestimmt werden. Für den Vergleich mit der Theorie wird die Abhängigkeit der Dispersionsrelation von den experimentellen Parametern Spannung, Zellhöhe und Zellneigung bestimmt. (2) Die Änderung der Kupferionenkonzentration unmittelbar an den Elektroden geht mit einer Veränderung der Dichte des Elektrolyten einher. Diese führt je nach Elektrode zu einer Auf- oder Abwärtsströmung, die eine mit der Zeit anwachsende Konvektionsrolle antreibt. Das Entstehen dieser Konvektionsrolle lässt sich unterbinden, indem die Zelle in einer vertikalen Konfiguration betrieben wird. Diese unterdrückt jedoch auch die Fingerbildung. Zur Untersuchung des Strömungsfeldes in der Zelle werden dem Elektrolyten Tracerpartikel hinzugefügt und deren Bahnen mit Hilfe des Programmpaketes Artemis verfolgt. Ein Vergleich der an der Anode gemessenen Strömungsgeschwindigkeiten mit der Theorie von Chazalviel et al. [J. Electroanal. Chem. 407, 61 (1996)] zeigt befriedigende Ergebnisse. An der Katode schiebt das wachsende Deposit die Konvektionsrolle vor sich her, so dass deren Ausdehnung gegen einen festen Wert konvergiert.Ein Vergleich der Ausrichtung der Konvektionsrolle mit den Normalenvektoren der Fingerhüllkurve zeigt, dass zu Beginn der Instabilität die Entwicklung der Grenzlinie der des Strömungsfeldes vorauseilt. (3) Die während eines Experimentes dissipierte elektrische Energie führt aufgrund des geringen Elektrolytvolumens zu einer messbaren Erwärmung. Dies wirft die Frage auf, ob hierbei Temperaturgradienten enstehen und zu Dichtegradienten führen, die die von den Konzentrationsunterschieden getriebenen Konvektionsrollen beeinflussen. Messungen des Temperaturfeldes mit einer Infrarotkamera zeigen, dass der Beitrag der Temperaturgradienten zur gesamten Dichtedifferenz kleiner als 4% bleibt.

Disordered spherical bead packs are anisotropic - Schröder-Turk, Gerd; Mickel, Walter; Schröter, Matthias; Delaney, Gary; Saadatfar, Mohammad; Senden, T.J.; Mecke, Klaus; Aste, T. (EPL - Europhysics Letters, 2010)
Investigating how tightly objects pack space is a long-standing problem, with relevance for many disciplines from discrete mathematics to the theory of glasses. Here we report on the fundamental yet so far overlooked geometric property that disordered mono-disperse spherical bead packs have significant local structural anisotropy manifest in the shape of the free space associated with each bead. Jammed disordered packings from several types of experiments and simulations reveal very similar values of the cell anisotropy, showing a linear decrease with packing fraction. Strong deviations from this trend are observed for unjammed configurations and for partially crystalline packings above 64%. These findings suggest an inherent geometrical reason why, in disordered packings, anisotropic shapes can fill space more efficiently than spheres, and have implications for packing effects in non-spherical liquid crystals, foams and structural glasses.

Experimental investigation of the initial regime in fingering electrodeposition: Dispersion relation and velocity measurements - Schröter, Matthias; Rehberg, Ingo; Kassner, Klaus; Claret, Josep; Sagués, Francesc (Physical Review E, 2002)
Recently a fingering morphology, resembling the hydrodynamic Saffman-Taylor instability, was identified in the quasi-two-dimensional electrodeposition of copper. We present here measurements of the dispersion relation of the growing front. The instability is accompanied by gravity-driven convection rolls at the electrodes, which are examined using particle image velocimetry. While at the anode the theory presented by Chazalviel et al. [J. Electroanal. Chem. 407, 61 (1996)] describes the convection roll, the flow field at the cathode is more complicated because of the growing deposit. In particular, the analysis of the orientation of the velocity vectors reveals some lag of the development of the convection roll compared to the finger envelope. © 2002 The American Physical Society.

Fingering instability in a water-sand mixture - Schröter, Matthias; Lange, Adrian; Scherer, Michael A.; Engel, Andreas; Rehberg, Ingo (European Physical Journal B, 1998)
The temporal evolution of a water-sand interface driven by gravity is experimentally investigated. By means of a Fourier analysis of the evolving interface the growth rates are determined for the different modes appearing in the developing front. To model the observed behavior we apply the idea of the Rayleigh-Taylor instability for two stratified fluids. Carrying out a linear stability analysis we calculate the growth rates from the corresponding dispersion relations for finite and infinite cell sizes. Based on the theoretical results the viscosity of the suspension is estimated to be approximately 100 times higher than that of pure water, in agreement with other experimental findings.

Finger-like patterns in sedimenting water-sand suspensions - Schröter, Matthias; Engel, Andreas; Rehberg, Ingo; Lange, Adrian; Betat, André; Iori, Giulia; Völtz, Camilla (Physics Reports-Review Section of Physics Letters, 2000)
The temporal evolution of a water-sand interface driven by gravity is experimentally investigated. By means of a Fourier analysis of the evolving interface the growth rates are determined for the different modes appearing in the developing front. To model the observed behavior we apply the idea of the Rayleigh-Taylor instability for two stratified fluids. Carrying out a linear stability analysis we calculate the growth rates from the corresponding dispersion relations for finite and infinite cell sizes and compose those results with the experimental data. Alternatively, the situation of the sedimenting sand can be modeled by a two-dimensional cellular automaton. A qualitative similarity between that model and the experimental situation is obtained. © 2000 Elsevier Science B.V.
Keywords: 05.45. - a

Fluidization of granular media wetted by liquid He4 - Schröter, Matthias; Herminghaus, Stephan; Huang, Kai; Sohaili, Masoud (Physical Review E, 2009)
We explore experimentally the fluidization of vertically agitated polymethylmethacrylate spheres wetted by liquid He4. By controlling the temperature around the λ point, we change the properties of the wetting liquid from a normal fluid (helium I) to a superfluid (helium II). For wetting by helium I, the critical acceleration for fluidization (Γc) shows a steep increase close to the saturation of the vapor pressure in the sample cell. For helium II wetting, Γc starts to increase at about 75% saturation, indicating that capillary bridges are enhanced by the superflow of the unsaturated helium film. Above saturation, Γc enters a plateau regime where the capillary force between particles is independent of the bridge volume. The plateau value is found to vary with temperature and shows a peak at 2.1 K, which we attribute to the influence of the specific heat of liquid helium. © 2009 The American Physical Society.

Focus on imaging methods in granular physics - Amon, Axelle; Born, Philip; Daniels, Karin; Dijksman, Joshua; Huang, Kai; Parker, David; Schröter, Matthias; Stannarius, Ralf; Wierschem, Andreas (Review of Scientific Instruments, 2017)
UnivIS-Import:2018-02-22:Pub.2017.tech.ITC.stmmec.focuso

Formation of Patterns in Granular Materials - Rehberg, Ingo; Scherer, Michael A.; Schröter, Matthias; Betat, André; Dury, Christian M.; Ristow, Gerald H.; Straßburger, Gunther (Evolution of Spontaneous Structures in Dissipative Continuous Systems, 1998)
In order to study the behaviour of fluidized granular material experimentally and numerically, we propose to investigate pattern-forming processes, because they can be easily observed and quantitatively characterized. We report measurements on five such systems, namely pattern formation of granular material i) by segregation, under the influence of ii) linear horizontal and iii) circular horizontal vibration, iv) water shear flow, and in v) a sedimenting suspension

Geometry-induced asymmetric diffusion - Schröter, Matthias; Shaw, Robert S.; Packard, Norman; Swinney, Harry L. (Proceedings of the National Academy of Sciences of the United States of America, 2007)
Past work has shown that ions can pass through a membrane more readily in one direction than the other. We demonstrate here in a model and an experiment that for a mixture of small and large particles such asymmetric diffusion can arise solely from an asymmetry in the geometry of the pores of the membrane. Our deterministic simulation considers a two-dimensional gas of elastic disks of two sizes diffusing through a membrane, and our laboratory experiment examines the diffusion of glass beads of two sizes through a metal membrane. In both experiment and simulation, the membrane is permeable only to the smaller particles, and the asymmetric pores lead to an asymmetry in the diffusion rates of these particles. The presence of even a small percentage of large particles can clog a membrane, preventing passage of the small particles in one direction while permitting free flow of the small particles in the other direction. The purely geometric kinetic constraints may play a role in common biological contexts such as membrane ion channels. © 2007 by The National Academy of Sciences of the USA.
Keywords: Asymmetric pores; Channels

Granular transport in a horizontally vibrated sawtooth channel - Schröter, Matthias; Mobarakabadi, Shahin; Oskoee, Ehsan Nedaaee; Habibi, Mehdi (Physical Review E, 2013)
We present a new mode of transport of spherical particles in a horizontally vibrated channel with sawtooth-shaped side walls. The underlying driving mechanism is based on an interplay of directional energy injection transformed by the sidewall collisions and density-dependent interparticle collisions. Experiments and matching numerics show that the average particle velocity reaches a maximum at 60% of the maximal filling density. Introducing a spatial phase shift between the channel boundaries increases the transport velocity by an order of magnitude. © 2013 American Physical Society.

High refractive index immersion liquid for superresolution 3D imaging using sapphire-based aplanatic numerical aperture increasing lens optics - Laskar, Junaid M.; Kumar, P. Shravan; Herminghaus, Stephan; Daniels, Karen E.; Schröter, Matthias (Applied Optics, 2016)
Optically transparent immersion liquids with refractive index (𝑛∼1.77) to match the sapphire-based aplanatic numerical aperture increasing lens (aNAIL) are necessary for achieving deep 3D imaging with high spatial resolution. We report that antimony tribromide (SbBr3) salt dissolved in liquid diiodomethane (CH2I2) provides a new high refractive index immersion liquid for optics applications. The refractive index is tunable from 𝑛=1.74 (pure) to 𝑛=1.873 (saturated), by adjusting either salt concentration or temperature; this allows it to match (or even exceed) the refractive index of sapphire. Importantly, the solution gives excellent light transmittance in the ultraviolet to near-infrared range, an improvement over commercially available immersion liquids. This refractive-index-matched immersion liquid formulation has enabled us to develop a sapphire-based aNAIL objective that has both high numerical aperture (NA=1.17) and long working distance (WD=12  mm). This opens up new possibilities for deep 3D imaging with high spatial resolution.

Influence of friction on granular segregation - Schröter, Matthias; Swinney, Harry L.; Ulrich, Stephan (Physical Review E, 2007)
Vertical shaking of a mixture of small and large beads can lead to segregation where the large beads either accumulate at the top of the sample, the so-called Brazil nut effect (BNE), or at the bottom, the reverse Brazil nut effect (RBNE). Here we demonstrate experimentally a sharp transition from the RBNE to the BNE when the particle coefficient of friction increases due to aging of the particles. This result can be explained by the two competing mechanisms of buoyancy and sidewall-driven convection, where the latter is assumed to grow in strength with increasing friction.

Influence of ohmic heating on the flow field in thin-layer electrodeposition - Schröter, Matthias; Claret, Josep; Kassner, Klaus; Rehberg, Ingo; Sagués, Francesc (Physical Review E, 2002)
In thin-layer electrodeposition the dissipated electrical energy leads to a substantial heating of the ion solution. We measured the resulting temperature field by means of an infrared camera. The properties of the temperature field correspond closely with the development of the concentration field. In particular, we find that the thermal gradients at the electrodes act similar to a weak additional driving force to the convection rolls driven by concentration gradients.

Jammed Frictional Tetrahedra are Hyperstatic - Schröter, Matthias; Neudecker, Max; Ulrich, Stephan; Herminghaus, Stephan (Physical Review Letters, 2013)
We prepare packings of frictional tetrahedra with volume fractions phi ranging from 0.469 to 0.622 using three different experimental protocols under isobaric conditions. Analysis via x-ray microtomography reveals that the contact number Z grows with phi, but does depend on the preparation protocol. While there exist four different types of contacts in tetrahedra packings, our analysis shows that the edge-to-face contacts contribute about 50% of the total increase in Z. The number of constraints per particle C increases also with phi and even the loosest packings are strongly hyperstatic, i.e., mechanically over-determined with C approximately twice the degrees of freedom each particle possesses.

(untitled)
In particulate soft matter systems the average number of contacts extitZ of a particle is an important predictor of the mechanical properties of the system. Using x-ray tomography, we analyze packings of frictional, oblate ellipsoids of various aspect ratios α, prepared at different global volume fractions ϕ extitg

Measuring the configurational temperature of a binary disc packing - Schröter, Matthias; Zhao, Song-Chuan (Soft Matter, 2014)
Jammed packings of granular materials differ from systems normally described by statistical mechanics in that they are athermal. In recent years a statistical mechanics of static granular media has emerged where the thermodynamic temperature is replaced by a configurational temperature X which describes how the number of mechanically stable configurations depends on the volume. Four different methods have been suggested to measure X. Three of them are computed from properties of the Voronoi volume distribution, the fourth takes into account the contact number and the global volume fraction. This paper answers two questions using experimental binary disc packings: first we test if the four methods to measure compactivity provide identical results when applied to the same dataset. We find that only two of the methods agree quantitatively. This implies that at least two of the four methods are wrong. Secondly, we test if X is indeed an intensive variable; this becomes true only for samples larger than roughly 200 particles. This result is shown to be due to recently measured correlations between the particle volumes [Zhao et al., Europhys. Lett., 2012, 97, 34004].

Mechanisms in the size segregation of a binary granular mixture - Schröter, Matthias; Swinney, Harry L.; Ulrich, Stephan; Kreft, Jennifer; Swift, Jack B. (Physical Review E, 2006)
A granular mixture of particles of two sizes that is shaken vertically will in most cases segregate. If the larger particles accumulate at the top of the sample, this is called the Brazil-nut effect (BNE); if they accumulate at the bottom, it is called the reverse Brazil-nut effect (RBNE). While this process is of great industrial importance in the handling of bulk solids, it is not well understood. In recent years ten different mechanisms have been suggested to explain when each type of segregation is observed. However, the dependence of the mechanisms on driving conditions and material parameters and hence their relative importance is largely unknown. In this paper we present experiments and simulations where both types of particles are made from the same material and shaken under low air pressure, which reduces the number of mechanisms to be considered to seven. We observe both BNE and RBNE by varying systematically the driving frequency and amplitude, diameter ratio, ratio of total volume of small to large particles, and overall sample volume. All our results can be explained by a combination of three mechanisms: a geometrical mechanism called void filling, transport of particles in sidewall-driven convection rolls, and thermal diffusion, a mechanism predicted by kinetic theory. (c) 2006 American Institute of Physics.

Migrating Shear Bands in Shaken Granular Matter - Kollmer, Jonathan; Shreve, Tara; Claussen, Joelle; Gerth, Stefan; Salamon, Michael; Uhlmann, Norman; Schröter, Matthias; Pöschel, Thorsten (Physical Review Letters, 2020)
When dense granular matter is sheared, the strain is often localized in shear bands. After some initial transient these shear bands become stationary. Here, we introduce a setup that periodically creates horizontally aligned shear bands which then migrate upward through the sample. Using x-ray radiography we demonstrate that this effect is caused by dilatancy, the reduction in volume fraction occurring in sheared dense granular media. Further on, we argue that these migrating shear bands are responsible for the previously reported periodic inflating and collapsing of the materia

Neutron Tomography as a Tool to Study Immiscible Fluids in Porous Media without Chemical Dopants - Schröter, Matthias; Murison, Julie; Moosavi, Robabeh; Schulz, Michael; Schillinger, Burkhard (Energy & Fuels, 2015)
We present the first study of fluid distribution inside porous media imaged by neutron tomography. We demonstrate that this technique has matured sufficiently to deliver pore level results. The major advantage of neutron tomography is the contrast mechanism of using deuterated phases. This allows high contrast imaging without the need to add large amounts of inorganic salts as dopants, required to achieve adequate contrast for X-ray tomography studies. Measurements were performed at the Antares beamline (MLZ, Garching) with a voxel size of 11.8 μm. We propose this technique as a useful tool for studying mutliphase phenomena in porous media where the results are known to depend on the salinty and species of ions present, such as low salinity water, surfactant, and polymer flooding.

Non-universal Voronoi cell shapes in amorphous ellipsoid packs - Schröter, Matthias; Schaller, Fabian; Kapfer, Sebastian; Hilton, James E.; Cleary, Paul W.; Mecke, Klaus; de Michele, Christiano; Schilling, Tanja; Saadatfar, Mohammad; Delaney, Gary; Schröder-Turk, Gerd (EPL - Europhysics Letters, 2015)
In particulate systems with short-range interactions, such as granular matter or simple fluids, local structure determines the macroscopic physical properties. We analyse local structure metrics derived from the Voronoi diagram of oblate ellipsoids, for various aspect ratios and global packing fractions φg. We focus on jammed static configurations of frictional ellipsoids, obtained by tomographic imaging and by discrete element method simulations. The rescaled distribution of local packing fractions φl, defined as the ratio of particle volume and its Voronoi cell volume, is found to be independent of the particle aspect ratio, and coincide with results for sphere packs. By contrast, the typical Voronoi cell shape, quantified by the Minkowski tensor anisotropy index β = β02,0, points towards a difference between random packings of spheres and those of oblate ellipsoids. While the average cell shape β of all cells with a given value of is similar in dense and loose jammed sphere packings, the structure of dense and loose ellipsoid packings differs substantially such that this does not hold true.

Onset of mechanical stability in random packings of frictional spheres - Schröter, Matthias; Jerkins, Melissa; Swinney, Harry L.; Saadatfar, Mohammad; Aste, T.; Senden, T.J. (Physical Review Letters, 2008)
Using sedimentation to obtain precisely controlled packings of noncohesive spheres, we find that the volume fraction phi(RLP) of the loosest mechanically stable packing is in an operational sense well defined by a limit process. This random loose packing volume fraction decreases with decreasing pressure p and increasing interparticle friction coefficient mu. Using x-ray tomography to correct for a container boundary effect that depends on particle size, we find for rough particles in the limit p -> 0 a new lower bound, phi(RLP)=0.550 +/- 0.001.

Performance of polarization-based stereoscopy screens - Schröter, Matthias; Fischer, Cornelius; Zhang, Xiaozhu; Hantke, Kristian (3D Research, 2012)
The screen is a key part of stereoscopic display systems using polarization to separate the different channels for each eye. The system crosstalk, characterizing the imperfection of the screen in terms of preserving the polarization of the incoming signal, and the scattering rate, characterizing the ability of the screen to deliver the incoming light to the viewers, determine the image quality of the system. Both values will depend on the viewing angle. In this work we measure the performance of three silver screens and three rear-projection screens. Additionally, we measure the surface texture of the screens using white-light interferometry. While part of our optical results can be explained by the surface roughness, more work is needed to understand the optical properties of the screens from a microscopic model.[Figure not available: see fulltext.] © 2012 3D Display Research Center and Springer-Verlag Berlin Heidelberg.
Keywords: ghosting; polarization; screen; stereoscopic projection; surface texture; system crosstalk

Phase transition in a static granular system - Schröter, Matthias; Radin, Charles; Swinney, Harry L.; Nägle, Sibylle (EPL - Europhysics Letters, 2007)
We find that a column of glass beads exhibits a well-defined transition between two phases that differ in their resistance to shear. Pulses of fluidization are used to prepare static sedimented states with well-defined particle volume fractions phi in the range 0.57-0.63. The resistance to shear is determined by slowly inserting a rod into the column of beads. Force measurements and bed height measurements both indicate that the transition occurs at phi = 0.60 for a range of speeds of the rod. Copyright (C) EPLA, 2007.

Segregation of simulated rfid markers during handling and transport of wheat - Schröter, Matthias; Steinmeier, Ulrich; Neudecker, Max; Witt, Annette; von Hörsten, Dieter (Transactions of the ASABE, 2014)
The ability to mark bulk goods from different origins with RFID markers is of industrial interest, as such a method would improve the traceability of, e.g., cereals. However, due to a number of open technical questions, this method has not been utilized on a larger scale yet. This article studies the amount of segregation occurring between RFID markers, which are simulated as grain-sized plastic capsules, and marked wheat using two different setups. This segregation could occur during handling and transport due to the slightly different physical properties of the markers and the grains; it would then lead to erroneous results during subsequent quantitative analysis. In the first experiment, two samples of wheat, one marked with RFID dummies, were discharged in several steps from a test silo. A comparison of the marker concentration in the samples with the amount of associated wheat showed no discernible segregation. An additional statistical analysis allowed us to establish a relationship between the marker concentration and the error margin. In the second experiment, a mixture of wheat and markers was vertically shaken in a container, mimicking transport of wheat in large vessels. The position of the markers inside the container was determined by three-dimensional scans using x-ray tomography. We found that shaking induced some segregation due to sidewall-driven convection rolls, which indicated that the simulated markers were not optimally matched to the wheat grains. © 2014 American Society of Agricultural and Biological Engineers.
Keywords: Bulk good; Computed tomography; Marking; Shaker; Silo; Traceability

Shearing of frictional sphere packings - Schröter, Matthias; Métayer, Jean-François; Suntrup III, Donald J.; Radin, Charles; Swinney, Harry L. (EPL - Europhysics Letters, 2011)
We measure shear response in packings of glass beads by pulling a thin, rough, metal plate vertically through a bed of volume fraction , which is set, before the plate is pulled, in the range from 0.575 to 0.628. The yield stress is velocity independent over 4 decades and increases exponentially with , with a transition at ≈0.595. An analysis of the measured force fluctuations indicates that the shear modulus is significantly smaller than the bulk modulus. © 2011 Europhysics Letters Association.

Sound speed in water-saturated glass beads as a function of frequency and porosity - Schröter, Matthias; Argo IV, Theodore F.; Guild, Matthew D.; Wilson, Preston S.; Radin, Charles; Swinney, Harry L. (Journal of the Acoustical Society of America, 2011)
Sound propagation in water-saturated granular sediments is known to depend on the sediment porosity, but few data in the literature address both the frequency and porosity dependency. To begin to address this deficiency, a fluidized bed technique was used to control the porosity of an artificial sediment composed of glass spheres of 265 mu m diameter. Time-of-flight measurements and the Fourier phase technique were utilized to determine the sound speed for frequencies from 300 to 800 kHz and porosities from 0.37 to 0.43. A Biot-based model qualitatively describes the porosity dependence. (C) 2011 Acoustical Society America

Stationary state volume fluctuations in a granular medium - Schröter, Matthias; Swinney, Harry L.; Goldman, Daniel I. (Physical Review E, 2005)
A statistical description of static granular material requires ergodic sampling of the phase space spanned by the different configurations of the particles. We periodically fluidize a column of glass beads and find that the sequence of volume fractions phi of postfluidized states is history independent and Gaussian distributed about a stationary state. The standard deviation of phi exhibits, as a function of phi, a minimum corresponding to a maximum in the number of statistically independent regions. Measurements of the fluctuations enable us to determine the compactivity X, a temperaturelike state variable introduced in the statistical theory of Edwards and Oakeshott [Physica A 157, 1080 (1989)].

Statistical mechanics for static granular media: open questions - Schröter, Matthias; Ciamarra, Massimo Pica; Richard, Patrick; Tighe, Brian P. (Soft Matter, 2012)
The theoretical description of granular materials, or assemblies of macroscopic particles, is a formidable task. Not only are granular materials out of thermal equilibrium, but they are also characterized by dissipative interactions and by static friction. Following a suggestion by S. F. Edwards, researchers have investigated the possible existence of a statistical mechanics of static granular systems, which would permit the description of macroscopic properties of mechanically stable granular assemblies from just a few parameters. The formulation and the validity of such an approach is still a matter of debate. This "emerging area'' focuses on three important questions concerning such a statistical mechanics approach. First, we consider how the phase space of interest is affected by the requirement of mechanical stability. Second, we explore how the intensive parameters analogous to temperature can be determined from experimental or numerical data. Finally, we contrast different ways to express the granular counterpart to the classical Hamiltonian, known as the volume function.

Structural similarity between dry and wet sphere packings - Weis, Simon; Schröder-Turk, Gerd; Schröter, Matthias (New Journal of Physics, 2019)
The mechanical properties of granular materials change significantly in the presence of a wetting liquid which creates capillary bridges between the particles. This results e.g. in a reduced value of the volume fraction when a packing is prepared with added liquid. Here we use x-ray tomography to demonstrate that this change in mechanical properties is not accompanied by structural differences between dry and wet sphere packings when compared at the same volume fraction. We characterize the structure of the packings by the average numbers of contacts of each sphere < Z > and the shape isotropy <beta(2,0)(0)> of the Voronoi cells of the particles. Additionally, we show that the number of liquid bridges per sphere < B > is approximately equal to < Z > + 2, independent of the volume fraction of the packing. These findings will be helpful in guiding the development of both particle-based models and continuum mechanical descriptions of wet granular matter.
CRIS-Team WoS Importer:2019-04-30

Tailoring the frictional properties of granular media - Schröter, Matthias; Utermann, Sonia; Aurin, Philipp; Benderoth, Markus; Fischer, Cornelius (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2011)
A method of modifying the roughness of soda-lime glass spheres is presented, with the purpose of tuning interparticle friction. The effect of chemical etching on the surface topography and the bulk frictional properties of grains are systematically investigated. The surface roughness of the grains is measured using white-light interferometry and characterized by the lateral and vertical roughness length scales. The underwater angle of repose is measured to characterize the bulk frictional behavior. We observe that the coefficient of friction depends on the vertical roughness length scale.

The mechanism of long-term coarsening of granular mixtures in rotating drums - Schröter, Matthias; Finger, Tilo; Stannarius, Ralf (New Journal of Physics, 2015)
Three fundamental segregation and pattern formation processes are known in granular mixtures in a rotating cylindrical drum: radial segregation, axial banding, and coarsening of the band pattern. While the mechanism for the first effect is well understood and for the second effect, several models have been proposed, the long-term coarsening mechanism remained unexplained so far. We demonstrate that the unidirectional flow between the bands in an axially segregated pattern is driven by small differences in size of the small beads at the band edges. Due to a process of microsegregation inside each band of small particles, which was so far unrecognized, this difference in diameter will be effective in all experiments with polydisperse beads. In consequence the stability of individual bands can be easily controlled by minor alterations of their composition. Our results make evident that a new mechanism as the driving force behind the axial particle flow has to be sought. We suggest possible hypotheses for such a mechanism.
Keywords: axial segregation; coarsening dynamics; granular mixtures; microsegregation; rotating drum

Tomographic Analysis of Jammed Ellipsoid Packings - Schröter, Matthias; Schaller, Fabian; Neudecker, Max; Saadatfar, Mohammad; Delaney, Gary; Mecke, Klaus; Schröder-Turk, Gerd (American Institute of Physics, 2013)
Disordered packings of ellipsoidal particles are an important model for disordered granular matter. Here we report a way to determine the average contact number of ellipsoid packings from tomographic analysis. Tomographic images of jammed ellipsoid packings prepared by vertical shaking of loose configurations are recorded and the positions and orientations of the ellipsoids are reconstructed. The average contact number can be extracted from a contact number scaling (CNS) function. The size of the particles, that may vary due to production inaccuracies, can also be determined by this method.
Keywords: Granular matter; Ellipsoids; Tomography; Contact numbers

Upper bound on the Edwards entropy in frictional monodisperse hard-sphere packings - Schröter, Matthias; Baranau, Vasili; Zhao, Song-Chuan; Scheel, Mario; Tallarek, Ulrich (Soft Matter, 2016)
We extend the Widom particle insertion method [B. Widom, J. Chem. Phys., 1963, 39, 2808-2812] to determine an upper bound s on the Edwards entropy in frictional hard-sphere packings. s corresponds to the logarithm of the number of mechanically stable configurations for a given volume fraction and boundary conditions. To accomplish this, we extend the method for estimating the particle insertion probability through the pore-size distribution in frictionless packings [V. Baranau, et al., Soft Matter, 2013, 9, 3361-3372] to the case of frictional particles. We use computer-generated and experimentally obtained three-dimensional sphere packings with volume fractions φ in the range 0.551-0.65. We find that s has a maximum in the vicinity of the Random Loose Packing Limit φ = 0.55 and decreases then monotonically with increasing φ to reach a minimum at φ = 0.65. Further on, s does not distinguish between real mechanical stability and packings in close proximity to mechanical stable configurations. The probability to find a given number of contacts for a particle inserted in a large enough pore does not depend on φ, but it decreases strongly with the contact number.

Wetting Heterogeneities in Porous Media Control Flow Dissipation - Schröter, Matthias; Murison, Julie; Semin, Benoît; Baret, Jean-Christophe; Herminghaus, Stephan; Brinkmann, Martin (Physical Review Applied, 2014)
Pressure-controlled displacement of an oil-water interface is studied in dense packings of functionalized glass beads with well-defined spatial wettability correlations. An enhanced dissipation is observed if the typical extension xi of the same-type wetting domains is smaller than the average bead diameter d. Three-dimensional imaging using x-ray microtomography shows that the frequencies n(s) of residual droplet volumes s for different xi collapse onto the same curve. This indicates that the additional dissipation for small xi is due to contact line pinning rather than an increase of capillary break-up and coalescence events.